Geriatric urinary tract infections: The value of laboratory parameters in estimating the need for bacteremia and Intensive Care Unit - Tartar, Ayse Sagmak; Balin, Safak Ozer (Professional Medical Publications, 2019)
Objective: We investigated the geriatric patients diagnosed as urinary tract infection and evaluated the effects of white blood cell (WBC), neutrophil count, platelet, mean platelet volume (MPV), red cell distribution width (RDW), total bilirubin, direct bilirubin, creatine, albumin, erythrocyte sedimentation rate, C-reactive protein, and neutrophil/lymphocyte ratio parameters on estimating the need for bacteremia and intensive care (IC) for the patients with pyelonephritis. Methods: Between 2016-2017, a total number of 188 patients aged 65 years and above were retrospectively evaluated at the infectious diseases clinic. Results: The 124 (66%) of the patients were male and 64 (34%) were female. The laboratory values of the patients with pyelonephritis and urosepsis were found to be significantly lower in only RDW bacteremic patients (p=0.047). The laboratory values during the application of third-step IC unit patients, who were treated and discharged, were compared. Albumin was significantly lower, while direct bilirubin, AST and ALT were significantly higher (p<0.05). Conclusions: Patients, whose biochemical parameters have changed, especially during admission or follow-up, should be evaluated carefully in terms of urosepsis, multiple organ failure and IC need. A number of diagnostic tests have been described to predict the need for sepsis and IC. However, many of them cannot be performed in emergency conditions. It is a great advantage that the parameters we use in our work are easily accessible and can be performed in emergency conditions.
Keywords: Urinary tract infection; Intensive Care; Biochemical Parameters; Geriatrics